Fighting software piracy: which governance tools matter in Africa? - Simplice A. Asongu; Antonio R. Andrés (African Governance and Development Institute (AGDI), 2012)
This article integrates previously missing components of government quality into the governance-piracy nexus in exploring governance mechanisms by which global obligations for the treatment of IPRs are effectively transmitted from international to the national level in the battle against piracy. It assesses the best governance tools in the fight against piracy and upholding of Intellectual Property Rights (IPRs). The instrumentality of IPR laws (treaties) in tackling piracy through good governance mechanisms is also examined. Findings demonstrate that: (1) while all governance tools under consideration significantly decrease the incidence of piracy, corruption-control is the most effective weapon; (2) but for voice and accountability, political stability and democracy, IPR laws (treaties) are instrumental in tackling piracy through government quality dynamics of rule of law, regulation quality, government effectiveness, corruption-control, and press freedom. Hence, the need for a policy approach most conducive to expanding development is to implement an integrated system of both IPRs and corollary good governance policies. Moreover, our findings support the relevance of good governance measures in developing countries wishing to complement their emerging IPR regimes.
Keywords: K42; O34; O38; O47; O57; 330; Software piracy; Governance tools; Intellectual property rights; Instrumental variables